P18 The use of a delegate induction before starting simulation scenario. (5th November 2017) - Gay, Christopher
Abstract : Background: The Foundation Acute Clinical Emergencies Simulation (FACES) course has ran for 3 years, with each 15 day programme seeing over 150 Foundation doctors welcomed into our simulation environment. FACES has 6 scenarios, with a mixture of simulated patients, actors and manikins. It was understood that experience of simulation practises would vary amongst the doctors, so a delegate induction was created to familiarise them with how HILS conducts its simulation exercises. Project Description: An initial grouping of two induction areas was created – environmental and manikin. 'Manikin' would cover what the high fidelity SimMan3G manikin can and can't do, and 'Environmental' would cover the rest such as phones, props, sharps and camera recording. One of the key themes present throughout the induction is the concept of a 'safe' learning environment. We reinforce that it's better to make mistakes in simulation than on a real patient, and today's event is not an assessment, and video recording is only used for debrief purposes than deleted routinely. Delivery of the induction is done by the lead technician for the event, and feedback after each event lead to changes and improvements being made over the course of each year. New faculty are also present at the induction so they are familiar with the tone of the day. Outcomes: The light hearted nature of the induction, paired with a thorough hands on with the manikin appears to result in less feedback from the delegates related to the suspension of disbelief and not knowing when to 'pretend'. Occasionally we do receive feedback that a particular element wasn't clear, and introduce new guidance to avert confusion. For example- delegates were sometimes confused when cubicle curtains were drawn back by the nurse – it was explained that this was so the cameras can see, rather than the nurse displaying a lack of privacy. Conclusions: As simulation activity becomes the norm, it may become less important to induct delegates on the principles of simulation before an event, however each simulation event has its own way of running, and it is this that is most important for the delegates to be inducted upon. Those investing in a well thought out induction can hope to immerse their delegates in realistic, though provoking and engaging simulation scenarios. Not doing so, risks a lack of delegate engagement, potential safety risks and poor feedback.